Perceived nutrition benefits and socio-demographic factors affecting consumption of forest foods in eastern and southern Cameroon - Fungo, R.; Tieguhong, J.C.; Muyonga, John H.; Odjo, S.; Tchingsabe, O.; Tchatat, M. (African Journals Online, 2018)
African forests act as sources of both plant and animal foods that provide significant amounts of nutrients and healthy boosting bioactive compounds. This study investigated the relationship between knowledge, perceptions and socio-demographic attributes towards consumption of forest foods. A total of 279 females in charge of decision making with respect to food preparation, were randomly selected from 12 villages in southern and eastern Cameroon, and interviewed using researcher administered questionnaires. Multivariate logistic regression analysis was used to identify the socio demographic factors and perceptions affecting consumption of forest foods. Baillonella toxisperma (African pearwood) (98%), Irvingia gabonesis (bush mango) (81%) and Trichoscypha abut (Mvout) (70%) were identified as the most nutritious foods. Among the animal forest foods, bush meat (11%) and Imbrasia spp. (edible caterpillars) (10%) were identified as the most nutritious. Consumption of forest foods was higher among polygamous families and also positively related to length of stay in the forest area, as well as age of female respondents. Education had an inverse relationship with use of forest foods. Perception towards the nutritional value of forest foods were also found to positively influence consumption of forest foods. Since negative perceptions were found to influence consumption, there is need to invest in awareness campaigns to strengthen the current knowledge levels among the study population.